2023
DOI: 10.3390/catal13010164
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ε-caprolactones) Initiated by Chiral Compounds: A New Protocol to Support Organocatalysts

Abstract: This work investigates the support of organocatalysts in polyesters, a class of polymers seldom used for this purpose. The proposal is to use the hydroxyl groups present in the structure of the chosen chiral compounds to promote the polymerization of ε-caprolactone, generating the support and anchoring the organocatalyst in a single step. A very simple method, with acid catalysis, was employed, that showed versatility in generating supported catalysts with different structures and functional groups and modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Thus, this Special Issue is dedicated to the field of organocatalysis and the latest developments regarding the optimization of the organocatalysts using distinct methodologies, with the commitment of meeting the environmental requirements, highlighting the importance of green solvents and catalyst recycling, as well as the need to correlate the waste produced in relation to the useful product for upscaling purposes [2][3][4][5][6][7][8], as briefly described in the following paragraphs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this Special Issue is dedicated to the field of organocatalysis and the latest developments regarding the optimization of the organocatalysts using distinct methodologies, with the commitment of meeting the environmental requirements, highlighting the importance of green solvents and catalyst recycling, as well as the need to correlate the waste produced in relation to the useful product for upscaling purposes [2][3][4][5][6][7][8], as briefly described in the following paragraphs.…”
mentioning
confidence: 99%
“…According to the authors, products could be recovered with good efficiency via supercritical CO 2 extraction. Likewise, Jacoby et al [3] demonstrated the feasibility of recovering products and catalysts through the development of novel polyestersupported catalysts (PCL) prepared from poly(ε-caprolactones), modulating the molecular weights in order to control the catalyst/polymer weight ratio, ensuring homogeneous catalysis, while allowing the catalysts to recover through CO 2 supercritical extraction. In terms of catalyst performance, the presence of amide groups decorating the catalysts' structures was more effective than the presence of their ester group counterparts toward the aldol product, achieving a higher degree of steroselectivity.…”
mentioning
confidence: 99%